Enhancing Cabernet Sauvignon wine quality with Merlot improver: A study on flavor and quality impact through various blending techniques - Fangfang Wang; Huan Wang; Qinquan Fu; Xinyi Ma; Min Zhao; Yinqi Liu; Kaiwen Liu; Bin Wang; Xuewei Shi (Journal of Agriculture and Food Research)
To investigate the effects of Merlot grape on improving the quality of Cabernet Sauvignon wine, nutrition, color, taste, and volatile components of the blending wine with Cabernet Sauvignon grape and Merlot grape under different concentrations and different blending methods were studied by using HPLC and HS-SPME-GC-MS. The results showed that adding 20 % Merlot grapes was able to observably increase the functional composition, color, and aromatic complexity of the Cabernet Sauvignon wine, in which the increased tartaric and malic acid content imparted citrus aromas to the wines. Furthermore, compared to co-wine blending, co-fermentations were more effective in increasing aromatic complexity, with a significant increase in flavor compounds such as ethyl acetate, isoamyl acetate, and isoamyl lactate, which endued the wine with intense fruity flavors. The results will provide a theoretical basis for improving the flavors of Cabernet Sauvignon wine.